2019
DOI: 10.3928/02793695-20190306-01
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth in Mental Health Nursing Education: Health Care Simulation With Remote Presence Technology

Abstract: The feasibility of integrating remote presence technology within a simulation scenario for psychiatric–mental health nursing (PMHN) students to develop telehealth competencies was evaluated. A wireless, audiovisual robot from Double® Robotics, maneuverable by smartphone or tablet computer, was used to simulate the facilitation of students' patient assessment and treatment decisions from a distant location for 32 weeks (total hours of robotic simulation = 32). Qualitative data were collected to assess student a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Due to the addition of human-computer interaction, the mental needs of college students are expanded (Brenda Happell et al, 2019 ). For the researchers, more attention should be given to the features and more care should be given to the students who are not paid attention to their study in the class instead of the top students in the traditional classroom, so that all the students can be treated equally (Danesh et al, 2019 ; Petchamé et al, 2021 ).…”
Section: Data Analysis and Test Resultsmentioning
confidence: 99%
“…Due to the addition of human-computer interaction, the mental needs of college students are expanded (Brenda Happell et al, 2019 ). For the researchers, more attention should be given to the features and more care should be given to the students who are not paid attention to their study in the class instead of the top students in the traditional classroom, so that all the students can be treated equally (Danesh et al, 2019 ; Petchamé et al, 2021 ).…”
Section: Data Analysis and Test Resultsmentioning
confidence: 99%
“…There are also robots that are designed to assist nurses by training and preparing them for the use of new technologies. Danesh et al [16] focused on the robot RoboAPRN, which uses remote presence telehealth technology designed to provide remote communication and assessments to prepare nursing students in using telecommunication, through a simulation lab especially on psychiatric/mental health care delivery [17].…”
Section: Nursing Assistance and Service Roboticsmentioning
confidence: 99%
“…Robots were used in general education to grade assignments, provide tutoring, create an opportunity for students to develop skills, and promote successful learning through the idea that the robot will not judge if students make mistakes. [13][14][15][16] Related to nursing education, the use of telepresence robots enabled educational institutions to deliver education in a creative and safe way. 9 Sampsel et al 6 used robots to teach a 1-hour clinical laboratory learning experience remotely.…”
mentioning
confidence: 99%
“…Telepresence robots are beginning to be applied to distance education and used in rural areas. 6,11 A study by Danesh et al 14 found students valued telepresence robotics during a psychiatric mental health simulation. Shaw et al 17 used telepresence robots to conduct remote pediatric clinical simulations.…”
mentioning
confidence: 99%